CeRuGe and CeRuSi: Heavy fermion systems with some unusual features - Sereni, Julian Gustavo Renzo (2010)
We have investigated the physical properties of CeRuSi, its homologue CeRuGe and some doped La alloys. All of them present similar properties: large paramagnetic temperatures θP ≈ -100 K and the level off of χ(T) below ≈ 10 K in coincidence with the maximum decrease of ρ(T), which starts to drop below 25 K. The respective γ(CeRuSi) ' 0.18 and γ(CeRuGe) ' 0.15 J/molK2 coefficients reveal a heavy fermion character, with a Kondo temperature TK ≈ 50 K comparable to the crystal field splitting. In both compounds a broad maximum in CP (T)/T is observed around 5 K, whose origin is yet not clear. In contrast to the usual behavior observed in Kondo lattice systems, when Si is replaced by Ge TK ∝ θP and 1/γ practically does not decreases despite the unit cell volume of CeRuGe is about 3% larger than that of CeRuSi. We discuss possible origins for these unusual features.